Pengaruh Teknologi Terhadap Perkembangan Finansial Islam di Indonesia - Layyinatus Shifah; Marliyah Marliyah (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
The development of digital technology has significantly impacted various economic sectors, including the Islamic financial sector. This article aims to analyze how technology contributes to the growth of Islamic finance in Indonesia. It discusses the role of Islamic fintech in financial inclusion, challenges in implementing technology in Islamic financial systems, and strategic opportunities to strengthen the position of Islamic finance in the digital era. The novelty of this study lies in the integrative analysis of current technologies such as blockchain and AI with regulations and their implementation in the context of Islamic finance in Indonesia, which has not been widely explored in previous literature.